Stability of Genome Composition and Recombination between Homoeologous Chromosomes in Festulolium (Festuca × Lolium) Cultivars - Kopecký, David; Šimoníková, Denisa; Ghesquière, Marc; Doležel, Jaroslav (Cytogenetic and genome research, 2017)
Festulolium are hybrids between fescue (Festuca) and ryegrass (Lolium) species and combine high seed yield of ryegrasses with abiotic stress tolerance of fescues. Chromosomes of Festuca and Lolium present in Festulolium freely pair and recombine, which results in highly variable progeny where every single plant has a unique chromosome constitution. Thus, the stability of the genomic composition in Festulolium cultivars is an important issue. In this work, we used in situ hybridization to examine the genomic composition (understood as the proportion of parental genomes present) over 3 consecutive generations of propagation via outcrossing (the first one being the generation used for cultivar registration) of 3 Festulolium cultivars. Our analysis revealed that the genome composition largely differs among the plants from individual cultivars but appears to be relatively stable over the generations. A gradual shift in the genome composition towards Lolium observed in the early generations of hybrids appears to reach a plateau where the proportions of parental genomes become stabilized. Nevertheless, the proportion remains unbalanced to a certain extent (always in favor of the Lolium genome) in each cultivar. Our observations indicate a possibility to modulate genomic composition in hybrids by breeders' selection without a compromise on stability.
Keywords: genom rostlinný; Aneuploidy; Lolium; aneuploidie; homologní rekombinace; Chromosomes, Plant; jílek; Genome, Plant; Homologous Recombination; chromozomy rostlin; Festuca